(untitled) (Research, Society and Development, 2021)
Acne vulgaris is a pathology that affects most teenagers, being of both sexes, it is more prevalent in males because of the change in hormones that occur at this stage. For this reason, many adolescents face serious psychological problems that generate low self-esteem, which can lead to depression and isolation from society. This study aims to assess the understanding that adolescents have about the necessary care to treat acne. A quantitative/qualitative exploratory research was carried out with adolescents and young people aged between 14 and 20 years old, attending a church in the city of São Luís – MA. The study sample comprised 13 participants who were initially instructed to answer the pre-intervention questionnaire available in the Socrative by MasteryConnect program, and the link to access the questionnaire was made available on the Google Meet platform, this questionnaire included 7 questions related to the main doubts related to the topic of acne. After everyone answered the form, the presentation of the lecture began, addressing the main information on the topic, as well as the main doubts of the studied public. At the end of the lecture, the study audience was again directed to through a link, so that they could answer the post-intervention questionnaire with the same questions. It is concluded with this work that adolescents need guidance about acne in their daily lives and the approach to this subject must be incisive in their daily lives.